Al-mashakil al-muta'alliqah bi-qadaya lamma shaml al-'a'ilat al-Filastiniyyah wa tasarih al-ziyarah (Markaz al-Ma'lumat al-Badilah, 1993)
'Problems relating to the reunification of Palestinian families and visit permits'